2018
DOI: 10.1155/2018/7943786
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Patterns ofCampylobacterspp. Isolated from Broiler Chickens in the North of Tunisia

Abstract: The aim of the current study is to assess the prevalence of Campylobacter infection in broiler chickens, raised in intensive production conditions, and to evaluate the antimicrobial susceptibility of recovered Campylobacter isolates. A total of 590 cloacal swab samples were taken from 13 broiler chicken flocks in the North East of Tunisia. All samples were tested for the presence of thermophilic Campylobacter by culture and PCR, targeting the mapA and ceuE genes, respectively. Susceptibility to antimicrobial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
39
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
(38 reference statements)
17
39
6
Order By: Relevance
“…Phenotypic characterization of Campylobacter isolates showed that poultry are colonized primarily by C. jejuni , followed by C. coli , and rarely by other species. These results are in agreement with the previous studies in the Netherlands [ 37 ] and Tunisia [ 17 ]. However , C. coli was isolated at a higher rate than C. jejuni in other studies in Egypt [ 38 ] and Ecuador [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Phenotypic characterization of Campylobacter isolates showed that poultry are colonized primarily by C. jejuni , followed by C. coli , and rarely by other species. These results are in agreement with the previous studies in the Netherlands [ 37 ] and Tunisia [ 17 ]. However , C. coli was isolated at a higher rate than C. jejuni in other studies in Egypt [ 38 ] and Ecuador [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…and Abushahba et al . reported lower prevalence rates of 22.4% and 23.5% in North Tunisia and Upper Egypt, respectively [ 17 , 18 ]. Furthermore, the rates previously reported in Algeria vary from 12% to 96% [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46] The resistance to fluoroquinolones is especially a concern as in many countries, the majority of Campylobacter isolates are no longer susceptible to this class of antibiotics. 18,[47][48][49][50] In the U.S., a recent CDC report revealed a rising trend of ciprofloxacin-resistant Campylobacter for the past two decades and the resistance rate reached 29% in 2017. 9 A unique feature of fluoroquinolone resistance in Campylobacter is its continued persistence or even increased prevalence in the absence of antibiotic usage.…”
Section: Antibiotic Resistance and Alternative Antibiotic Therapymentioning
confidence: 99%
“…For instance, in 2017, 57.7% of human and 68.8 of broiler isolates in the EU were ciprofloxacin resistant (European Food Safety AuthorityEuropean Centre for Disease Prevention and Control, 2019). In other parts of the world, up to 100% of all isolates were ciprofloxacin resistant (Gharbi et al, 2018;Li et al, 2017;Sierra-Arguello et al, 2016;Woźniak-Biel et al, 2018). Given the high prevalence of ciprofloxacin-resistant Campylobacter strains, ciprofloxacin has been largely abandoned for the treatment of human infections, with erythromicin being used as a replacement antibiotic to treat human infections (Bolinger & Kathariou, 2017).…”
Section: ! Discussionmentioning
confidence: 99%